Complete guide to foam rolling : increase flexibility and mobility, enhance recovery, minimize injury, optimize performance - Stull, Kyle, ....- (Champaigne : Human Kinetics, 2018)
Foam rolling may be one of the best kept secrets in sport, training, and fitness. Proven to stimulate blood flow, prepare muscles, improve mobility and flexibility, initiate the recovery process, and reduce muscle soreness, it is a secret worth sharing. Backed by scientific research, Complete Guide to Foam Rolling provides step-by-step instructions for 27 of the most effective foam rolling techniques for muscle preparation and recovery. Reduce pain and restore function with therapeutic movements that help rehabilitate your body and reduce the risk of injury. Learn to breathe, relax, and roll through tight spots as part of your warm-up, flexibility work, and recovery. Then adapt any of the ready-to-use protocols to create a customized program to address your specific problem areas as well as your overall muscle and nervous system needs. Invest in your training success by applying these proven self-massage techniques. Complete Guide to Foam Rolling is your path to better overall performance. Need continuing education? A companion continuing education exam is available for purchase. Contents Part I. Foundations Chapter 1. Science of Foam Rolling Chapter 2. Benefits of Foam Rolling Chapter 3. Foam Rolling Safety Chapter 4. Foam Rolling Equipment Part II. Techniques Chapter 5. Foot and Lower Leg Chapter 6. Upper Leg Chapter 7. Hips Chapter 8. Chest and Upper Back Chapter 9. Shoulders and Arms Part III. Programming Chapter 10. Full-Body Assessment Chapter 11. Warm-Up Chapter 12. Flexibility Chapter 13. Recovery Chapter 14. Rehabilitation References About the Author Audiences Exercise and fitness enthusiasts looking for alternatives or complements to traditional stretching as a way to prepare for and recover from a workout; personal trainers and strength coaches who wish to use these techniques with their clients.